The Saint, the Sea Monster, and an Invitation to a Dîner-Dansant: Ethnographic Reflections on the Edgy Passage — and the Double Edge — of Modernity, Mayotte 1975- 2001 - Lambek, Michael (Anthropologica, 2022)
This depiction of social change in the Western Indian Ocean emphasizes consciousness, agency, and temporal experience as Malagasy speakers are poised between grasping the future and completing—but also regretting—the past.